Earnings Dynamics and Inequality during Macroeconomic Turbulence: Sweden 1991-1999 - Magnus Gustavsson (Uppsala University, Department of Economics, 2002)
Using a rich longitudinal database, I study the dynamics behind changes in the distribution of annual earnings in Sweden 1991 to 1999. The analysis indicates a systematic increase in persistent earnings differentials during the 1990s; workers with low relative earnings in the beginning of the decade generally have lower relative earnings in the end. The evolution of transitory earnings fluctuations differs between age groups and matters the most for changes in earnings dispersion among younger workers. To shed some light on the role of wages behind the findings for earnings, wage dynamics is also studied. The results indicate that increased persistent wage inequality is one source behind the increase in persistent earnings inequality.
urn:nbn:se:uu:diva-4451
Keywords: C23; D31; J31; 330; Earnings dynamics; Earnings inequality; Wage structure; Einkommensverteilung; Lohnstruktur; Schweden